Popularyzacja archeologii na przykładzie rezerwatu archeologicznego w Kaliszu-Zawodziu - Przepiórka, Paulina (Folia Praehistorica Posnaniensia, 2022)
The subject of this article is the analysis of the activities conducted by the Archaeological Reserve in Kalisz-Zawodzie and its role in education and popularization of archaeology. It is based on the results of conducted quantitative and qualitative research surveys among visitors to the reserve and residents of Kalisz, including students of one of the primary schools, and interviews with experts. On their basis, the profile of visitors, the motivation they were guided by and their perception of the reserve and its offer were determined. In order to improve the image of the reserve and develop an appropriate offer, an original program and organizational concept for the discussed facility was created on the basis of the collected information.